Crosstalk between Mitochondrial and Sarcoplasmic Reticulum Ca2+ Cycling Modulates Cardiac Pacemaker Cell Automaticity - Yaniv, Yael; Spurgeon, Harold A.; Lyashkov, Alexey E.; Yang, Dongmei; Ziman, Bruce D.; Maltsev, Victor A.; Lakatta, Edward G. (PloS one, 2012)
Mitochondria dynamically buffer cytosolic Ca(2+) in cardiac ventricular cells and this affects the Ca(2+) load of the sarcoplasmic reticulum (SR). In sinoatrial-node cells (SANC) the SR generates periodic local, subsarcolemmal Ca(2+) releases (LCRs) that depend upon the SR load and are involved in SANC automaticity: LCRs activate an inward Na(+)-Ca(2+) exchange current to accelerate the diastolic depolarization, prompting the ensemble of surface membrane ion channels to generate the next action potential (AP). To determine if mitochondrial Ca(2+) (Ca(2+) (m)), cytosolic Ca(2+) (Ca(2+) (c))-SR-Ca(2+) crosstalk occurs in single rabbit SANC, and how this may relate to SANC normal automaticity. Inhibition of mitochondrial Ca(2+) influx into (Ru360) or Ca(2+) efflux from (CGP-37157) decreased [Ca(2+)](m) to 80 ± 8% control or increased [Ca(2+)](m) to 119 ± 7% control, respectively. Concurrent with inhibition of mitochondrial Ca(2+) influx or efflux, the SR Ca(2+) load, and LCR size, duration, amplitude and period (imaged via confocal linescan) significantly increased or decreased, respectively. Changes in total ensemble LCR Ca(2+) signal were highly correlated with the change in the SR Ca(2+) load (r(2) = 0.97). Changes in the spontaneous AP cycle length (Ru360, 111 ± 1% control; CGP-37157, 89 ± 2% control) in response to changes in [Ca(2+)](m) were predicted by concurrent changes in LCR period (r(2) = 0.84). A change in SANC Ca(2+) (m) flux translates into a change in the AP firing rate by effecting changes in Ca(2+) (c) and SR Ca(2+) loading, which affects the characteristics of spontaneous SR Ca(2+) release.